The Influence of the Moral Reasoning Learning Model on Social Awareness among Fifth-Grade Elementary Students in Cakranegara, Mataram - Ali Suria; Khairun Nisa; Asri Fauzi (Journal of General Education and Humanities, 2025)
This study aimed to assess the effectiveness of the Moral Reasoning learning model in enhancing social awareness among fifth-grade students in Cluster V Cakranegara, Mataram. A quantitative quasi-experimental Nonequivalent Control Group Design was used with 50 purposively sampled students divided equally into experimental and control groups. The experimental group received the Moral Reasoning model, while the control group received the Value Clarification Technique model. Data were collected using observations and a validated social awareness questionnaire. Independent samples t-test results indicated a significant effect of the Moral Reasoning model on students’ social awareness (p = 0.048, t = 2.030). However, normalised gain analysis showed minimal improvement (mean N-Gain = 0.015), indicating a low increase. This suggests that despite its statistical significance, the model’s practical effectiveness in substantially enhancing students’ social awareness remains limited. Implementation challenges included uneven group participation and insufficient depth of moral reflection. These findings imply that although the Moral Reasoning model has potential as an instructional strategy, effective facilitation and sufficient time allocation are essential to achieve meaningful outcomes. Further research with longer intervention periods and improved facilitation strategies is recommended to optimise its impact on fostering social awareness in elementary education.